2019
DOI: 10.1097/md.0000000000015041
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous sinus-orbital apex aspergillus infection in a diabetic patient

Abstract: Rationale: Cavernous sinus-orbital apex aspergillosis is a rare but serious complication of rhinosinusitis. Pathology results are scarce, and this condition is difficult to diagnose based on clinical and radiological results. Patient concerns: A 64-year-old woman presented with cavernous sinus-orbital apex syndrome. Axial and sagittal T1 contrast-enhanced magnetic resonance imaging (MRI) showed a right orbital apex mass abutting the right posterior ethmoid sinus, spheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
1
7
0
1
Order By: Relevance
“…Early debridement of necrotic tissue, isolation of the causative organism and institution of appropriate antifungal is the most likely cause for successful outcome in a disease which otherwise has high mortality as described in literature. This fact is echoed by all previously reported cases as well [6,[7][8][9][10][11][12].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Early debridement of necrotic tissue, isolation of the causative organism and institution of appropriate antifungal is the most likely cause for successful outcome in a disease which otherwise has high mortality as described in literature. This fact is echoed by all previously reported cases as well [6,[7][8][9][10][11][12].…”
Section: Discussionsupporting
confidence: 55%
“…All other cases described till date are in middle-aged and elderly adults. Some of the elderly adults had associated diabetes mellitus, but majority of them underwent only HIV serology to rule out associated immunodeficiency states [6,[7][8][9][10][11][12]. In the current case, apart from HIV serology and blood sugar, both quantitative and qualitative tests for T, B and NK cell were performed to rule out commonly inherited causes of immunodeficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Our case showed rhinofacial involvement. Vascular invasion is an important feature of rhino-cerebral mycosis by Mucorales ( Li and Lun, 2012 ; Li et al, 2014 ) and has been observed in rhino-orbital aspergillosis ( Ben-Ami et al, 2009 ; Huang and Gui, 2019 ). Whether or not the lethal cerebral hemorrhage was induced by the angiodestruction of the fungus could not be determined; angioinvasive and angiodestructive characteristics have been observed biopsied in the rhinofacial area.…”
Section: Discussionmentioning
confidence: 99%
“…Management of this should include consultation of an ophthalmologist and an ENT. Repeat imaging and endoscopic nasal surgery to biopsy should follow closely after [1,[4][5]. For uncomplicated infections, Gappy et al recommend that antibiotics should be continued until there is complete resolution: this can range up to at least two to three weeks of IV and PO antibiotic therapy [1].…”
Section: Managementmentioning
confidence: 99%